Determination of competency framework for technical and vocational education and training (TVET) educators in Nigerian tertiary institutions - Adamu, Mohammed Hamisu (2018)
Lack of competent TVET Educators in Nigerian institutions has led to several problems such as low quality graduates and unemployment. Competency is a vital element for assessing the quality of technical and vocational education and training (TVET) Educators. Therefore, this research investigated the TVET Educators ’ perceptions on competency needs in Nigerian tertiary institutions based on Malaysian Human Resource Development Practitioners (MHRDP) competency model for workplace learning and performance (WLP). Apart from that, this study also aimed at investigating the perception differences on competency elements among difference TVET tertiary institutions in order to enhance their quality. The study was fully quantitative and 218 questionnaires were systematically distributed to the TVET educators from five tertiary institutions based on the stratified sampling technique. A total of 205 questionnaires were returned. Descriptive and inferential statistical methods such as mean, EFA and ANOVA were used to analyse the data. The research found that Nigerian TVET educators perceived all the competency elements (25 constituents) as important; 19 out 25 constituents of competency framework were significantly related to Nigerian tertiary institutions. The research findings also revealed that there was no statistically significant differences among the TVET educators perception on competency elements across different types of TVET tertiary institutions. The developed competency framework for Nigerian TVET tertiary institutions contributes originally to the body of knowledge. The research recommends that government and other relevant authorities should emphasize on the implementation of the framework to tertiary institutions in Nigeria. A similar research should be undertaken to extend the result to reflect other Non-TVET educators in Nigeria.